2013
DOI: 10.1002/ar.22733
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Olfactory Bulb Neurogenesis

Abstract: The neurons in the olfactory bulb originate from molecularly defined and spatially distinct proliferative regions. Glutamatergic projection neurons are generated during the embryonic period in the local ventricular zone of the olfactory bulb, a territory in the dorsal telencephalon in which the transcription factor Pax6 is expressed. Some cells in this zone also express Tbr1, a marker of glutamatergic neurons. By contrast, embryonic olfactory bulb interneurons are derived from Gsx2 expressing cells in the dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 221 publications
(317 reference statements)
0
34
0
Order By: Relevance
“…The greater percentages of astrocytes differentiating from aOBSCs compared to those of neurons and oligodendrocytes are consistent with previous findings on the differentiation of aNSCs (Gritti et al, 2002; Sanai et al, 2004; Vergaño-Vera et al, 2009; Nieto-Estévez et al, 2013). Next, we investigated the effect of TRG on the expression of a key neurogenic gene, Ngn1 , and of genes involved in the generation of astrocytes ( Hes5 ) and oligodendrocytes (Olig2 ) (Table 2) (Vergaño-Vera et al, 2009; Díaz-Guerra et al, 2013; Imayoshi and Kageyama, 2014). Figure 3M shows that the three transcripts were expressed in cultures differentiating for 7 days (MTD, Table 1) with no significant changes being observed between conditions in controls and TRG.…”
Section: Resultsmentioning
confidence: 99%
“…The greater percentages of astrocytes differentiating from aOBSCs compared to those of neurons and oligodendrocytes are consistent with previous findings on the differentiation of aNSCs (Gritti et al, 2002; Sanai et al, 2004; Vergaño-Vera et al, 2009; Nieto-Estévez et al, 2013). Next, we investigated the effect of TRG on the expression of a key neurogenic gene, Ngn1 , and of genes involved in the generation of astrocytes ( Hes5 ) and oligodendrocytes (Olig2 ) (Table 2) (Vergaño-Vera et al, 2009; Díaz-Guerra et al, 2013; Imayoshi and Kageyama, 2014). Figure 3M shows that the three transcripts were expressed in cultures differentiating for 7 days (MTD, Table 1) with no significant changes being observed between conditions in controls and TRG.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we previously showed that high levels of Gsx2 inhibit OBSC self-renewal. Furthermore, in the light of studies from other laboratories, we suggest that the upregulation of Gsx2 in the mutant cells can be attributed to the reduced levels of Pax6 [12,13,61].…”
Section: Discussionmentioning
confidence: 99%
“…To explore the molecular mechanisms associated to the + Sey Dey mutation, the expression of TFs involved in the regulation of self-renewal (Sox2, Gsx2, Hes1, and Hes5) [9,12,60,61] and cell proliferation, and that of markers of NSCs and progenitors (Egfr, Fgf-1r, Fgf-2r, and Nestin) [10] was measured in aOBSCs (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations